Inventarisasi Permudaan Meranti (Shorea spp.) Pada Arboretum Kawasan Universitas Riau Kota Pekanbaru Provinsi Riau - Wahyu, Elvan; Sribudiani, Evi; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Meranti (Shorea spp.) is an important commodity which is one of the major timber producing commercial plants in Indonesia. In worldwide trading, meranti group is divided into four major groups, namely: group of red meranti, yellow meranti group, white meranti group and group of turvy meranti. Purpose of the implementation of this study was to determine the availability, amount, and regeneration dominance of meranti (Shorea spp.) as well as a tree diagram in the profile Riau University Arboretum area. Techniques of data collection is done by using the method purposive sampling or transect lines. Entire observation contains regeneration sample plots, namely regeneration meranti much as 9 rods (2.76%) while the 317 rods (97.24%) are type of non meranti. Meranti Shorea parvistipulata Heim and Shorea parvifolia were found. INP at a rate of 0% seedling, sapling rate of 2.28%, 15.20% for poles and tree level of 57.03%. Keyword : inventore, regeneration, meranti, arboretum